Telomerase and Non-Telomerase Mechanisms of Telomere Maintenance 2020
DOI: 10.5772/intechopen.86327
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and Telomerase Activity in the Human Placenta

Abstract: Placenta is a transient organ ensuring the intrauterine development of the individual. To meet fetal requirements, rapid and continuous cell proliferation enlarges the areas of tissues maintaining maternofetal transport. The cell division in placenta is accompanied with shortening of telomeres leading to cell senescence. Telomerase activity, on the other hand, ensures replication of telomeres and allows the organ to serve till the end of pregnancy. This balanced process may be negatively influenced by unfavora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
(195 reference statements)
0
5
0
Order By: Relevance
“…However, some meta-analyzed studies reported non-fasting glucose, glycosylated hemoglobin, and lipid results during delivery. Experimental studies suggest that adequate metabolic management of glucose metabolism might reduce the risk of telomere shortening [60]. Only two studies reported glycosylated hemoglobin, total cholesterol, HDL cholesterol, LDL cholesterol, and triglycerides that do not provide sufficient information compared to the available literature on their metabolism.…”
Section: Maternal Telomere Length and Gdmmentioning
confidence: 99%
“…However, some meta-analyzed studies reported non-fasting glucose, glycosylated hemoglobin, and lipid results during delivery. Experimental studies suggest that adequate metabolic management of glucose metabolism might reduce the risk of telomere shortening [60]. Only two studies reported glycosylated hemoglobin, total cholesterol, HDL cholesterol, LDL cholesterol, and triglycerides that do not provide sufficient information compared to the available literature on their metabolism.…”
Section: Maternal Telomere Length and Gdmmentioning
confidence: 99%
“…Telomere shortening induces cell senescence, apoptosis, or genome instability. Some papers showing that the telomere length in placenta decreases during pregnancy were published, but there are no unequivocal results of the assessment of telomere length in pathologic placentas [35]. As those studies were based mainly on the measurement of mean telomere length, the use of contemporary methods quantifying very short telomeres may better clarify processes related to placental senescence at the end of normal and pathologically complicated pregnancies [36,37].…”
Section: Proliferative Potential In Term Placentamentioning
confidence: 99%
“…Placental aging is a normal phenomenon, which was first described in the 70s, but only during the latest decade has the association between placental aging and various changes during pregnancy been studied. Nevertheless, in some cases the placental cells' aging occurs prematurely, disrupting their normal function [15,16]. Various factors may affect the pace of aging of the placenta, proper fetal development, and birth outcomes, including maternal dietary intake and nutritional status [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, TL and telomerase (i.e., the enzyme responsible for maintenance of the length of telomeres by the addition of guanine-rich repetitive sequences), have been investigated as possible biomarkers of premature placental aging [15,16]. Physiologically, cell division is accompanied by TL shortening that leads towards the aging trajectory.…”
Section: Introductionmentioning
confidence: 99%